2005
DOI: 10.2172/923075
|View full text |Cite
|
Sign up to set email alerts
|

A joint computational and experimental study to evaluate Inconel-sheathed thermocouple performance in flames.

Abstract: A joint experimental and computational study was performed to evaluate the capability of the Sandia Fire Code VULCAN to predict thermocouple response temperature. Thermocouple temperatures recorded by an Inconel-sheathed thermocouple inserted into a near-adiabatic flat flame were predicted by companion VULCAN simulations. The predicted thermocouple temperatures were within 6% of the measured values, with the error primarily attributable to uncertainty in Inconel 600 emissivity and axial conduction losses along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 4 publications
(3 reference statements)
2
16
0
Order By: Relevance
“…In this manner, the flow field, the local convection coefficient to the thermocouple, an estimate of the soot volume fraction, the path length for radiation, all can be taken into account so that the thermocouple reading can be interpreted. A presentation of such an effort is discussed extensively in [4]. Although there is still some unresolved uncertainty, this study found that such a fire code can account for more than 90% of the 800 °C discrepancy noted above.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In this manner, the flow field, the local convection coefficient to the thermocouple, an estimate of the soot volume fraction, the path length for radiation, all can be taken into account so that the thermocouple reading can be interpreted. A presentation of such an effort is discussed extensively in [4]. Although there is still some unresolved uncertainty, this study found that such a fire code can account for more than 90% of the 800 °C discrepancy noted above.…”
Section: Introductionmentioning
confidence: 77%
“…For both the sheathed 10 mil thermocouple and the bare thermocouple used in the present experiments, the time constant was found from the Omega Temperature Handbook [8] to be on order of 0.5 seconds in a particular flowing hot air stream. While there will be some physical differences between combustion gases and air, from [4], the time constant for a 62 mil, sheathed thermocouple inserted into clean flame gases was 5 seconds; the corresponding value from [8] was 6 seconds.…”
Section: Thermocouple Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium tube is 53 cm and it can safely be assumed that the particles investigated in this study are at flow conditions by the time they exit the equilibrium tube. [38] for oxidized Inconel was digitized and a fourth order polynomial was used to reconstruct the curve for this calculation. Inconel is a nickel alloy similar to that used for the test fixture and it is assumed that the two materials have the same emissivity.…”
Section: Figure 5: Dust Feed Boxmentioning
confidence: 99%
“…The benefits of these diagnostics are that the probes are robust, inexpensive and simple to implement. However, these probes are intrusive, which disturbs the environment being investigated, and suffer from bias errors resulting from thermal lag as well as radiative and conductive heat transfer with the surroundings [6]. The high resolution demanded by the models coupled with the above mentioned bias errors have resulted in the recent adaptation by the Sandia fire community toward laser or optically based diagnostics, which include imaging techniques such as planar laser-induced fluorescence for scalar imaging and particleimage velocimetry [4,7], emission spectroscopy [8], tunable-diode-laser absorption spectroscopy (TDLAS) for species, soot and temperature determinations [9] and in situ pyrometric probes [10].…”
Section: Introductionmentioning
confidence: 99%